A Multicenter Performance Evaluation of a Blood Glucose Monitoring System in 21 Leading Hospitals in Spain. (January 2016) - Bedini, José Luis; Wallace, Jane F.; Petruschke, Thorsten; Pardo, Scott
Background: Self-monitoring of blood glucose is crucial for the effective self-management of diabetes. The present study evaluated the accuracy of the Contour® XT blood glucose monitoring system (BGMS) compared to the reference method in a large multicenter study under routine lab conditions at each hospital site. Methods: This study was conducted at 21 leading hospitals in Spain using leftover whole blood samples (n = 2100). Samples were tested with the BGMS using 1 commercial strip lot and the local laboratory hexokinase method. BGMS accuracy was assessed and results were compared to ISO 15197:2013 accuracy limit criteria and by using mean absolute relative difference analysis (MARD), consensus (Parkes) error grid (CEG), and surveillance error grid analyses (SEG). Results: Pooled analysis of 2100 measurements from all sites showed that 99.43% of the BGMS results were within the ranges accepted by the accuracy limit criteria. The overall MARD was 3.85%. MARD was 4.47% for glucose concentrations < 70 mg/dL and 3.81% for concentrations of 70-300 mg/dL. In CEG, most results (99.8%) were within zone A ("no effect on clinical action"); the remaining ones (0.2%) were in zone B ("little to no effect on clinical action"). The SEG analysis showed that most of the results (98.4%) were in the "no risk" zone, with the remaining results in the "slight, lower" risk zone. Conclusions: This is the largest multicenter study of Contour XT BGMS to date, and shows that this BGMS meets the ISO 15197:2013 accuracy limit criteria under local routine conditions in 21 leading Spanish hospitals.